Repeated sprint performance and metabolic recovery curves: Effects of aerobic and anaerobic characteristics - Alves de Aguiar, R.; Turnes, T.; Santos de Oliveira Cruz, R.; Salvador, A. F.; Caputo, F. (Applied Physiology, Nutrition, and Metabolism, 2015)
To examine the influence of aerobic and anaerobic indices on repeated sprint (RS) performance and ability (RSA), 8 sprinters (SPR), 8 endurance runners (END), and 8 active participants (ACT) performed the following tests: (i) incremental test; (ii) 1-min test to determine first decay time constant of pulmonary oxygen uptake off-kinetics and parameters related to anaerobic energy supply, lactate exchange, and removal abilities from blood lactate kinetics; and (iii) RS test (ten 35-m sprints, departing every 20 s) to determine best (RSbest) and mean (RSmean) sprint times and percentage of sprint decrement (%Dec). While SPR had a 98%-100% likelihood of having the fastest RSbest (Cohen`s d of 1.8 and 1.4 for ACT and END, respectively) and RSmean (2.1 and 0.9 for ACT and END, respectively), END presented a 97%-100% likelihood of having the lowest %Dec (0.9 and 2.2 for ACT and SPR, respectively). RSmean was very largely correlated with RSbest (r = 0.85) and moderately correlated with estimates of anaerobic energy supply (r = -0.40 to -0.49). RSmean adjusted for RSbest (which indirectly reflects RSA) was largely correlated with lactate exchange ability (r = 0.55). Our results confirm the importance of locomotor- and anaerobic-related variables to RS performance, and highlight the importance of disposal of selected metabolic by-products to RSA.